Comparison between low vs high cadence interval training sessions - Bosio, A.; Induni, M.; Menaspà, P.; Morelli, A.; Tornaghi, M.; Carlomagno, D.; Rampinini, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
SFR (uphill pedaling at low rpm) is a type of interval training (IT). High cadence cycling achieves higher cardio-respiratory and metabolic responses than low cadence, but decreases neuromuscular properties to the same extent (Hirai et al. 2010; Lepers et al., 2001). Low compared to high cadence IT seems a better strategy to improve uphill and flat time trial performance. Aim of the study was to compare the acute effects of two IT sessions. Methods: Low (35rpm, SFR) and high (115rpm, HC) cadence IT sessions (8x4min 2min rec) were carried out on 2 days. Workload was 64±2% of the aerobic peak power output. Heart rate (HR), oxygen uptake (VO2), blood lactate (La), and RPE were monitored. Quadriceps peak torque (PT), maximal rate of torque development and relaxation (MRTD, MRTR) were assessed by single (ST) and paired stimuli at 10 Hz (DB10) and 100 Hz (DB100). Maximal voluntary contraction (MVC) and activation (VA) were also noted. Measurements were performed at baseline (PRE), 5 and 20min after each session (POST5, POST20). Repeated measures ANOVA was used for analysis. Results: SFR determined lower (p<0.05) HR (140±13 vs 149±7), VO2 (2.664±0.297 vs 2.797±0.264), La (1.5±0.7 vs 2.4±1.1) than HC. RPE was similar (3.7±1.1 vs 3.7±1.2, p=0.734). MVC and VA decreased at POST5 (-9.5±6.7% and -3.9±5.0%; p<0.05) in SFR and HC, only VA recovered at POST20. PT ST decreased similarly at POST5 and recovered at POST20 only in HC (SFR: 49±8, 31±8, 41±8 Nm; HC: 48±7, 33±7, 46±8 Nm respectively at PRE, POST5, POST20; p=0.021). MRTD ST and DB10 (p<0.05) decreased similarly at POST5 but recovered at POST20 only in HC. MRTR DB100 decreased at POST5 and did not recover at POST20 just in SFR (1.14±0.31, 0.91±0.23, 1.03±0.19 and 1.19±0.31, 1.11±0.23, 1.19±0.24 N•m-1•ms-1 SFR, HC and PRE, POST5, POST20 respectively; p<0.05). Discussion: The locus of exercise-induced fatigue is not central. The decreased MRTR DB100 and the nonrecovery of PT and MRTD ST at POST20 support a more likely peripheral origin of fatigue during SFR, even with a lower physiological strain than HC. For each stroke, average torque is ~200% higher and applied for three times longer during SFR than HC. A greater blood flow restriction caused by a high level of muscle contraction (Lollgen et al., 1980) might be a reason for the greater peripheral fatigue induced by SFR.